Analysis of Wearing Masks Compliance among Palembang Residents during the Covid-19 Pandemic using the Health Belief Model (HBM) Construct - Dhandi Wijaya; Misnaniarti Misnaniarti; Rico Januar Sitorus (Alliance of Health Activists (AloHA), 2022)
Since it was first identified in China at the end of December 2019, Coronavirus disease 2019 (Covid-19) has quickly spread throughout the world, including Indonesia. Maintaining physical distance, washing hands, and wearing masks are very important in preventing the spread of Covid-19. Although the use of masks is relatively easy to do, the level of compliance with the use of masks in the Palembang is still low. This study aim was to analyze compliance in wearing masks among Palembang residents during the Covid-19 pandemic. This cross-sectional study was conducted on 400 Palembang residents aged ≥20 years who were taken by simple random sampling from 15 June to 15 July 2021. Data collection was carried out using an online questionnaire. The questionnaire consisted of questions regarding socio-demographics, statements regarding the HBM and compliance to wearing masks. Responses to statements of perception and compliance were scored using a 5-point Likert scale. Data were analyzed univariately, bivariate analysis using Chi-square test, and multivariate using logistic regression analysis. Bivariate analysis revealed that sex, education, and employment status were significant relationships to compliance to wearing masks (p0.05). Sex was a confounding variable and multivariate analysis showed only perceived severity and cues to action had a significant relationship with compliance to wearing masks after it was controlled by the sex variable (p